Are computers effective lie detectors? : a meta-analysis of linguistic cues todeception - Hauch, Valerie; Blandón-Gitlin, Iris; Masip, Jaume; Sporer, Siegfried L.; Justus Liebig University Giessen (My University, 2015)
This meta-analysis investigates linguistic cues to deception and whether these cues can be detected with computer programs. We integrated operational definitions for 79 cues from 44 studies where software had been used to identify linguistic deception cues. These cues were allocated to six research questions. As expected, the meta-analyses demonstrated that, relative to truth-tellers, liars experienced greater cognitive load, expressed more negative emotions, distanced themselves more from events, expressed fewer sensory perceptual words, and referred less often to cognitive processes. However, liars were not more uncertain than truth-tellers. These effects were moderated by event type, involvement, emotional valence, intensity of interaction, motivation, and other moderators. Although the overall effect size was small, theorydriven predictions for certain cues received support. These findings not only further our knowledge about the usefulness of linguistic cues to detect deception with computers in applied settings but also elucidate the relationship between language and deception.
Keywords: detection of deception; linguistic cues; computer program; meta-analysis; ddc:150